Fast-Track in Minimally Invasive Gynecology: A Randomized Trial Comparing Costs and Clinical Outcomes - Lambat Emery, Shahzia; Brossard, Philippe; Petignat, Patrick; Boulvain, Michel; Pluchino, Nicola; Dällenbach, Patrick; Wenger, Jean-Marie; Savoldelli, Georges L.; Rehberg-Klug, Benno; Dubuisson, Jean (Frontiers in Surgery, 2021)
Study Objective: Evaluate the effects of a fast-track (FT) protocol on costs and post-operative recovery. Methods: One hundred and seventy women undergoing total laparoscopic hysterectomy for a benign indication were randomized in a FT protocol or a usual care protocol. A FT protocol included the combination of minimally invasive surgery, analgesia optimization, early oral refeeding and rapid mobilization of patients was compared to a usual care protocol. Primary outcome was costs. Secondary outcomes were length of stay, post-operative morbidity and patient satisfaction. Main Results: The mean total cost in the FT group was 13,070 ± 4,321 Euros (EUR) per patient, and that in the usual care group was 3.5% higher at 13,527 ± 3,925 EUR (p = 0.49). The FT group had lower inpatient surgical costs but higher total ambulatory costs during the first post-operative month. The mean hospital stay in the FT group was 52.7 ± 26.8 h, and that in the usual care group was 20% higher at 65.8 ± 33.7 h (p = 0.006). Morbidity during the first post-operative month was not significantly different between the two groups. On their day of discharge, the proportion of patients satisfied with pain management was similar in both groups [83% in FT and 78% in the usual care group (p = 0.57)]. Satisfaction with medical follow-up 1 month after surgery was also similar [91% in FT and 88% in the usual care group (p = 0.69)]. Conclusion: Implementation of a FT protocol in laparoscopic hysterectomy for benign indications has minimal non-significant effects on costs but significantly reduces hospital stay without increasing post-operative morbidity nor decreasing patient satisfaction. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04839263.